On my watch : leading NATO in a time of war - Stoltenberg, Jens (W.W. Norton & Company, 2025)
"When Jens Stoltenberg took office as secretary general of NATO in 2014, the world was already changing. What followed was a decade marked by war, diplomatic crises, and decisions that helped shape the West's shared security. On My Watch takes readers behind closed doors and offers rare insight into how the world's most powerful military alliance handles crises. Stoltenberg describes the effort to keep NATO united and addresses key issues, such as the war in Ukraine, NATO's withdrawal from Afghanistan, relations with Russia and China, and cooperation with world leaders including Angela Merkel, Donald Trump, and Volodymyr Zelenskyy. This is not a book about division. It is a story of unity, of friendship -- and of why NATO still matters. Through his reflections on disagreements and dilemmas, he offers a unique view into the art of diplomacy and the hard choices that must be made when global peace is at stake. He ultimately shows why openness is essential to preserve cohesion -- and to face the challenges of tomorrow." --